Greenflation in the Era of Energy Transition: New Implications for Sustainable Economic Policy - Sukomardojo, Tekat; Patriani, Ira; Judijanto, Loso; Pratomo, Soni; Afrilia, Ufa Anita; Sari, Avid Leonardo (Global Writing Academica Researching & Publishing, 2024)
In the accelerating shift towards renewable energy, a phenomenon termed 'greenflation' is emerging as a critical factor influencing global economic policies. This paper delves into the concept of greenflation, characterized by the inflationary pressures stemming from the transition to green energy sources. Through a comprehensive literature review, we analyze the multifaceted impact of greenflation on sustainable economic policies. We explore the dynamics between the increasing demand for renewable energy resources and the corresponding rise in their prices, considering the implications for both developed and developing economies. The paper also examines how greenflation challenges traditional economic models and necessitates the formulation of innovative policy frameworks that balance environmental sustainability with economic stability. By synthesizing existing research, this study aims to provide a nuanced understanding of greenflation and its implications, paving the way for informed policy-making in the era of energy transition.